2005
DOI: 10.1002/uog.1788
|View full text |Cite
|
Sign up to set email alerts
|

Congenital renal tract anomalies: outcome and follow‐up of 402 cases detected antenatally between 1986 and 2001

Abstract: Objective To determine the long-term prognosis of antenatally detected renal tract anomalies in order to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 44 publications
3
43
1
2
Order By: Relevance
“…At baseline, the clinical data for our series were similar to the data reported in observational studies by showing a higher proportion of males and mild to moderate ANH (24)(25)(26). There has been an agreement among several studies that the degree of ANH is associated with postnatal outcome (8,13).…”
Section: Discussionsupporting
confidence: 87%
“…At baseline, the clinical data for our series were similar to the data reported in observational studies by showing a higher proportion of males and mild to moderate ANH (24)(25)(26). There has been an agreement among several studies that the degree of ANH is associated with postnatal outcome (8,13).…”
Section: Discussionsupporting
confidence: 87%
“…In our study, there was a predominance of urinary tract dilatation (62%), and the mortality rate in this group varied according to kidney involvement (12-64%). In another follow-up study at a tertiary center, Damen-Elias et al [43] found a similar proportion of urinary tract dilatation (61%) and a comparable mortality rate (13.4%) for this group. In addition, they also reported a significant increase in mortality rate among patients with structural kidney anomalies (50.6%).…”
Section: Discussionmentioning
confidence: 53%
“…Damen-Elias HA et al (2001), chromosomal studies on amniotic fluid should be offered in cases with renal malformation; the incidence of chromosomal abnormality in has reported to be 8-12% 16 .…”
Section: Discussionmentioning
confidence: 99%